Obstetric Telephone Triage - Engeltjes B; Wouters E; Rijke R; Scheele F (Dove Medical Press, 2020)
Bernice Engeltjes,1,2 Eveline Wouters,3 Rudy Rijke,2 Fedde Scheele1 1Athena Institute of Transdisciplinary Research, VU University Amsterdam, Amsterdam, the Netherlands; 2School of Health Care Studies, Rotterdam University of Applied Sciences, Rotterdam, the Netherlands; 3Department of Tranzo, School of Social and Behavioral Sciences, Tilburg University, Tilburg, the NetherlandsCorrespondence: Bernice EngeltjesSchool of Health Care Studies, Rotterdam University of Applied Sciences, Rochussenstraat 198, Rotterdam 3015 EK, the NetherlandsTel +31 6 41804881Email engeltjesbernice@gmail.comObjective: Little is known about obstetric telephone triage: the methods used to prioritize the severity of symptoms of obstetric emergency and other unplanned care requests originating by telephone. In large-scale obstetric units, there is a need for an evidence-based triage guideline. The aim of this study was to develop an obstetric guideline for telephonic triage.Design, Setting and Participants: A multi-phase multi-center study was performed with consecutive drafts of the triage guideline using four focus groups, four observations of training sessions and two expert consultations based on the Delphi method. The study was performed in ten hospitals in the Netherlands. The obstetric care professionals involved were gynecologists, midwives, nurses, doctor’s assistants, team managers and application managers. After each focus group, each observation and each expert consultation, an interpretative analysis was undertaken. Based on these analyses, the obstetric telephone triage guideline was drafted.Measurements and Results: The designed guideline describes the primary symptoms presented, five prioritization categories and several descriptors. Consensus (> 90%) was reached during the second expert consultation. Fifty-seven (91.9%) participants stated that the obstetric telephone triage guideline was clinically complete, correct, user-friendly and well designed, and 61 (98.4%) participants judged that the newly designed triage guideline was ready to use in daily practice.Key-Conclusions and Implications for Practice: An evidence-based guideline for obstetric telephone triage was developed through a multi-phase multi-center study with all stakeholders. The guideline was found to be clinically complete, correct, well-designed and user-friendly. It provides a uniform and concrete basis for assessing the severity of the symptoms of obstetric emergency and other unplanned care requests originating by telephone. It also provides a good basis to further develop this evidence-based guideline for telephone triage by continuous registration of all calls.Keywords: midwifery, obstetric telephone triage, triage guideline, unplanned telephone obstetric care